2006
DOI: 10.1111/j.1523-5378.2006.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori in Georgian Patients with Dyspepsia

Abstract: We confirmed that among individuals in Georgia, the prevalence of H. pylori is high and cagA-positive strains were equally present among H. pylori-positive patients with PUD and NUD and asymptomatic persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
4
9
0
Order By: Relevance
“…In the current study, the prevalence of cagA among patients infected with H. pylori was 70%, which was in accordance with reports from Iraq (71%) and Turkey (78%) [25,29]. It was also consistent with reports from Europe and North America [30,34]. However, the prevalence obtained from the present study was lower than that reported from Southeast Asia (93% positive for cagA) by a similar metaanalysis study [35].…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the prevalence of cagA among patients infected with H. pylori was 70%, which was in accordance with reports from Iraq (71%) and Turkey (78%) [25,29]. It was also consistent with reports from Europe and North America [30,34]. However, the prevalence obtained from the present study was lower than that reported from Southeast Asia (93% positive for cagA) by a similar metaanalysis study [35].…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that there should be certain factors other than H. pylori infection to induce peptic ulcer disease in children. Moreover, H. pylori-related peptic ulcer diseases in children with abdominal pain were less frequent (1.1-1.3%) than in dyspeptic adults (17.7-72.7%) [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The annual incidence rate of H. pylori infection is ≈4%-15% in developing countries, compared with ≈0.5% in industrialized countries (4). Studies in the Republic of Georgia (ROG), a developing country with an economy in transition, suggested that >70% of adults are infected with H. pylori (5,6) and that the prevalence rate of gastric cancer is 18 cases per 100,000 population, ≈6-to 9-fold higher than in the United States (National Center for Disease Control, Tbilisi, ROG, unpub. data, 2003).…”
Section: Helicobacter Pylori Infection In Patients Undergoing Upper Ementioning
confidence: 99%